Acceptance and commitment therapy meets peer-support. Development of a supportive self-care intervention for patients with rare diseases: a multistage development process - Bernd Löwe; Natalie Uhlenbusch; Miriam K Depping (BMJ Open)
Objective We aimed at developing a patient-centred self-help programme, tailored to the needs of patients with rare chronic diseases.Design Multistage, multimethod development process including a survey with validated self-report scales and open-ended questions (phase 1) and focus groups (phase 2) for needs assessment and, consolidating the first phases and the literature, the intervention development (phase 3).Setting Phase 1: nationwide online survey in Germany, phase 2: four separate and diagnostically homogeneous focus groups. The focus groups took place at a university medical centre in Germany.Participants Target group were patients with rare diseases that occur at a prevalence <1:2000. Phase 1: n=300 participants with different rare diseases. Phase 2: Individuals with neurofibromatosis type 1 (n=4), primary sclerosing cholangitis (n=5), pulmonary arterial hypertension (n=4) and Marfan syndrome (n=5).Results The central results of phases 1 and 2 were requests for more information about the disease and contact with other affected persons. Patients also expressed support needs in dealing with difficult emotions and identified acceptance of the disease as a turning point for quality of life. In phase 3, we identified acceptance and commitment therapy (ACT) as a suitable therapeutic approach and determined details about implementation and execution of self-management programmes. A 6-week self-help concept led by peer counsellors was developed, which includes disease-specific information and ACT-based exercises.Conclusion Based on a multistage needs assessment, we developed a peer-guided self-help intervention for patients with rare chronic diseases. Combining self-management, peer-counselling and ACT may help living with a rare condition. Further research needs to test the programme’s efficacy.Trial registration number ISRCTN13738704.